Parenting and child well-being during the COVID-19 outbreak: The importance of marital adjustment and parental self-efficacy - Diniz, Eva (2021)
The pandemic situation of COVID-19 has introduced new challenges on family routines, affecting interpersonal relationships, which may have detrimental consequences to child well-being. The current study aimed to examine the direct effects of marital adjustment on child socioemotional adjustment and to test if parental self-efficacy mediated this association during home confinement due to COVID-19. A final sample of 163 caregivers was recruited online during home confinement period. On average children were 6 years-old (SD=2.92; 44.8% girls). Caregivers and their child were in home confinement for an average of 31 days (SD=12.08). Most of the couples had been married or living together for an average of 14 years (SD=5.77) and had a university degree, mostly living in metropolitan areas. Caregivers answer to a set of measures assessing marital adjustment, parental self-efficacy, and child socioemotional competence and behavior. Findings depicted a direct effect on the positive association between marital satisfaction and parental self-efficacy, and negatively associated with anger-aggression. Parental self-efficacy was positively associated with child’s: social competence, negatively associated with anger-aggression, and anxiety-withdrawal. Indirect effects depicted that marital satisfaction was associated with child’s social competence, anger-aggression and anxiety-withdrawal through parental self-efficacy. Thus, higher marital satisfaction was associated with more parental self-efficacy which in turn was associated with more child’s social competence. Findings are relevant to the current state of the art, given the lack of information regarding imposed isolation due to COVID-19 and the consequences it may have to child’s well-being.